Business Marketing Strategy for the Recovery of Spiritual Pilgrimage Tourism Visits to Holyland After the Covid-19 Pandemic Case Study at PT. Talitakum Tour & Travel in Jakarta - Papehe, Yulie (Universitas Syiah Kuala, 2023)
The type of research used in this study is qualitative. This research was conducted at PT. Talitakum Tour ; Traveler to find out how the recovery of Holyland's spiritual pilgrimage tourism after the Covid-19 pandemic COVID-19 pandemic Research shows that the Covid-19 pandemic The COVID-19 pandemic made the wheels of the economy stop instantly and the Tourism industry including spiritual pilgrimage tourism to Holyland became one of the worst businesses at that time. The data collected came from interviews, field observations, and documentation, the data sources of this study were secondary data and primary data. Technical analysis of this research data through data collection, data reduction, data presentation, and verification, The results of this study show that PT. Talitakum Tour ; Travel has also experienced the impact of COVID-19 pandeCOVID-19 has hit the world, 202From there there was no departure of the Hajj group to Holyland, the group to Holyland began to depart in June 2022 until now. At the beginning of the group's departure to Holyland, there were still health protocols such as PCR, but in the following months, there were no more health protocols or regulations related to Covid-19. The conclusion of this study is the decline in interest in ritual pilgrimage tourism to the Holyland by Christians after the Covid-19 pandemic, There has been a significant increase in ticket prices and difficulties in obtaining international flight tickets, but this phenomenon strengthens the revival of the tourism industry, customer satisfaction creates emotional bonds and good relations between PT. Talitakum Tour ; Travel and its customers, this is what helps PT. Talitakum Tour ; Travel can recover faster from the impact of the COVID-19 pandemic.